Pengaruh Penggunaan Media Biteable Terhadap Kemampuan Menulis Teks Deskripsi Siswa Kelas VII SMP Swasta Jambi Medan - Sri Rejeki Situmorang (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This research is motivated by a learning system that only focuses on teachers and books, with no sound, images or videos to support the activity of writing descriptive text. This research aims to determine the influence that occurs before and after using Biteable media on the ability to write descriptive text for class VII students. The competency standards to be achieved in this research are in the 2013 curriculum with KD 3.2 and 4.2. This research uses an experimental method with a one group design with data collection through observation, interviews, and administering pre-tests and post-tests. This research was conducted at Jambi Medan Private Middle School with class VII-A as the sample class used. Based on the research results, it can be seen that the pre-test score (before treatment) was 57.2 and the post-test score (after treatment) was 80.4. Based on the results of calculations that have been carried out using the t test, the value of tcount = 5.51 is obtained. After tcount is known, this value will then be consulted at a significance level of α = 0.05 and n = 29, obtained ttable = 2.045. Thus, it can be concluded that tcount > ttable, namely 5.51 > 2.045, so the alternative hypothesis (Hα) is accepted.